Use of microconidia for testing the genetic purity of Neurospora stocks - K K Adhvaryu; R Maheshwari (Fungal Genetics Reports, 2000)
Uninucleate microconidia have been used to check the purity of laboratory stocks of Neurospora. Stock cultures of N. crassa and N. intermedia become heterokaryotic due to spontaneous mutation.